American individualism and masculinity? The case of nursing homes. Issue 4 (1st October 2020) - Pacheco Baldó, Rosa M.
ABSTRACT: The aim of this article is to show that opposing cultural values can coexist in the same culture at a time. The United States is typically featured as a society representative of individualist and masculine cultural values. Nevertheless, the conditions given in some contexts collide head on with this view. The case that this article examines is one of these scenarios. The analysis of more than a hundred statements from fifteen nursing homes has shown that these centres try to convey messages compatible with tribal-group and feminine values. At a vulnerable time of life, as ageing is, owing to the need for assistance or to a desire to feel safe, what is attractive is knowing that one is going to be in a place of warmth. People seek for an environment of cooperation and care and not of competition and detachment. The discourse that these centres use to attract customers, opposes somehow the individualist and masculine values that are usually associated with the American culture. Therefore, this article discusses the importance of context and the communicative situation, which tilt the discourse used by the speakers even if it does not reflect the values traditionally assigned to their cultural group.